Integrating competency analysis into national rehabilitation workforce evaluation: a case study - Jody-Anne Mills; Weronika Krzepkowska; Alarcos Cieza; Paloma Cuchi; Pascal Zurn; Stephanie Doris Short; James W. Middleton (BMC, 2023)
Abstract Background Establishing a workforce capable of meeting population needs is contingent on evaluation that can inform sound policy and planning. Health workforce evaluation has traditionally relied on health labour market analysis and workload estimations. To date, competency analysis has not been included in national health workforce evaluation, despite that fact that the findings may go far in guiding decisions around workforce composition, optimisation and education and training. This case study sought to assess the feasibility and perceived added value of integrating competency analysis into national rehabilitation workforce evaluation, and to determine how competency analysis can shape rehabilitation workforce planning. The findings of the case study can be used to explore the integration of competency analysis in the evaluation of other health-related occupational groups. Methods Participant observation was complemented by key informant interviews with experts engaged in the national rehabilitation workforce evaluation in Poland. These experts represented stakeholders in policy, education, research, clinical practice and professional associations. Results The results indicated that competency analysis can be feasibly integrated into national rehabilitation workforce evaluation, particularly when implementation is supported through the use of online platforms. However, the collection of additional data using other tools, such as a survey of the behaviours and tasks of a wider sample of rehabilitation workers, could strengthen data reliability. Experts perceived findings of the competency analysis to be valuable for expanding the understanding of rehabilitation, shedding light on task allocation and deployment of the existing rehabilitation workforce, and advocating for the rehabilitation workforce to be strengthened, especially in relation to those occupations which may not be recognised or valued as rehabilitation workers. Although it was not possible to fully explore the impact of competency analysis data on rehabilitation workforce planning and development in this study, experts suggested that its availability would likely foster greater cooperation among occupations, which has been missing at the policy and planning level to date. It further demonstrates what competency data should be collected and reported, and provides richer information to guide decisions. Conclusions Competency analysis complements traditional labour market analysis and workload estimates, adding depth to the understanding of how members of the workforce perform and perceive themselves, and how deficiencies in the workforce impact on the provision of care to specific population groups.